Polystyrene Pocket Lithography: Sculpting Plastic with Light. Issue 27 (29th May 2022) - Samal, Pinak; Samal, Jay Rabindra Kumar; Gubbins, Eva; Vroemen, Pascal; van Blitterswijk, Clemens; Truckenmüller, Roman; Giselbrecht, Stefan
Abstract: Tissue‐culture‐ware polystyrene is the gold standard for in vitro cell culture. While microengineering techniques can create advanced cell microenvironments in polystyrene, they require specialized equipment and reagents, which hinder their accessibility for most biological researchers. An economical and easily accessible method is developed and validated for fabricating microstructures directly in polystyrene with sizes approaching subcellular dimensions while requiring minimal processing time. The process involves deep ultraviolet irradiation through a shadow mask or ink pattern using inexpensive, handheld devices followed by selective chemical development with common reagents to generate micropatterns with depths/heights between 5 and 10 µm, which can be used to guide cell behavior. The remarkable straightforwardness of the process enables this class of microengineering techniques to be broadly accessible to diverse research communities. Abstract : A direct deep ultraviolet (DUV) photolithography method, which enables fabrication of microstructures in bulk polystyrene cell culture substrates, is presented. Pipelines for generating ink‐based DUV masks and micropattern virtualization further increase the remarkable straightforwardness of the process. This, combined with the high applicability, can significantly improve accessibility of this class of microfabrication techniques to a broad biological research community.